Enhancing Entrepreneurial Skills and Pancasila Student Profiles through Digital Learning Tools in Science Education - Juanta, Palma; Festiyed, Festiyed; Diliarosta, Skunda; Lufri, Lufri; Yohandri, Yohandri; Moyo, Kgomotso (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research examines the effect of project-based learning (PjBL) assisted by ethnoscience animation videos on students problem-solving skills and their Pancasila character profile in science education. The study employed a quasi-experimental design to evaluate the impact of independent variables (PjBL and animated videos) on dependent variables (problem-solving skills and character development). The research objectives were to assess the effectiveness of the PjBL model in improving problem-solving skills and to determine its role in developing Pancasila character dimensions in students. The study involved students from classes VII-1 and VII-6 at Dr. Wahidin Sudirohusodo Middle School as the sample. Data collection included test instruments to measure problem-solving abilities and non-test instruments for assessing character dimensions of the Pancasila student profile. Results showed significant differences in the average scores of problem-solving skills between the experimental and control classes, with a significance value (2-tailed) of 0.00 < 0.05. Similarly, for the Pancasila student profile dimensions, the significance value was also 0.00 < 0.05, indicating a significant improvement in the experimental group. These findings confirm that the PjBL model assisted by ethnoscience animation videos is valid, practical, and effective for improving both problem-solving skills and character development. In conclusion, integrating PjBL with ethnoscience animation videos addresses the challenges in science education by aligning with skill-based and culturally relevant learning approaches. The model supports students cognitive and character development, making it suitable for application in the Society 5.0 era.